Proceso atención de enfermería en hemorragia post parto por rotura de cuello uterino. - Güillín Párraga, Derian Rafael (2022)
The present clinical case study of a nursing care process in a 24-year-old puerperal woman, in her second pregnancy by normal delivery, without presenting any abnormality during the trimesters of pregnancy. In the present case study with the nursing care process, a correct monitoring of the vital signs and the patient's hemodynamic activity was carried out, the administration of their medications prescribed by the doctor was carried out correctly. the nursing process helps the patient in her evolutionary improvement from the moment the red key was activated, following the respective protocols in said obstetric emergency, the needs raised by Virginia Henderson were used, in addition to the theory of NANDA, NIC and NOC which were fundamental in this care process since it also helped to determine which were the most important signs and symptoms to correct and treat them to avoid major complications in the puerperal woman.